Microflow Simulations via the Lattice Boltzmann Method (Communications in Computational Physics, 2020)
The exact solution to the hierarchy of nonlinear lattice Boltzmann kineticequations, for the stationary planar Couette flow for any Knudsen number was presentedby S. Ansumali et al. [Phys. Rev. Lett., 98 (2007), 124502]. In this paper, simulationresults at a non-vanishing value of the Knudsen number are compared withthe closed-form solutions for the higher-order moments. The order of convergence tothe exact solution is also studied. The lattice Boltzmann simulations are in excellentagreement with the exact solution.